Диверсионная война - Тамоников Александр Александрович (Тамоников, 2015)
Экземпляры: ф.2 (20171004) / Инвентарный номер: 49260 / Цена: 208.00 / Сис.шифр: Р2 / Авт.знак: Т 17 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6